Pengaruh media edukasi food model dua dimensi terhadap pemahaman label gizi dan pemilihan makanan sehat pada remaja - Nur Khoiriyah; Mahfuzhoh Fadillah Heryanda (Poltekkes Kemenkes Aceh, 2024)
Background: Poor food consumption behavior during adolescence can have an impact on health problems in adulthood. Improving understanding of nutrition label and healthy food choices through nutrition education is one effort to improve food consumption. Nutrition education can be carried out using various tools, one of which is two-dimensional food model.Objectives: To analyze the effect of nutrition education using two-dimensional food model on understanding of nutrition label and healthy food choices in adolescents.Methods: The design was quasi-experiment with intervention and control groups. The research was conducted at MTs Swasta Nurul Huda from August to September 2023 with 21 respondents in each treatment group. Data collected were respondent characteristics, understanding of nutrition label (knowledge, reading ability, and attitudes), and healthy food choices (knowledge and attitudes). Different tests were carried out between groups using the independent t-test and Mann-Whitney, and between baseline and endline using paired t-test and Wilcoxon test.Results: Knowledge and ability to read nutrition labels was significantly higher in the intervention group than in the control group (p=0,000 and p=0,005). However, attitudes towards nutrition labels did not differ significantly between treatment groups (p=0.193). knowledge and attitudes about healthy food choices were significantly higher in the intervention group than in the control group (p=0,000 and p=0,042).Conclusion: Nutrition education using two-dimensional food model media has an effect on nutrition label literacy skills and healthy food choices in adolescents